Size of TiO2 nanoparticles influences their phototoxicity : an in vitro investigation - Xiong, Sijing (2013)
To uncover the size influence of TiO2 nanoparticles on their potential toxicity, the cytotoxicity of different-sized TiO2 nanoparticles with and without photoactivation was tested. It was demonstrated that without photoactivation, TiO2 nanoparticles were inert up to 100 μg/ml. On the contrary, with photoactivation, the toxicity of TiO2 nanoparticles significantly increased, which correlated well with the specific surface area of the particles. Our results also suggest that the generation of hydroxyl radicals and reactive oxygen species (ROS)-mediated damage to the surface-adsorbed biomolecules could be the two major reasons for the cytotoxicity of TiO2 nanoparticles after photoactivation. Higher ROS generation from smaller particles was detected under both biotic and abiotic conditions. Smaller particles could adsorb more proteins, which was confirmed by thermogravimetric analysis. To further investigate the influence of the generation of hydroxyl radicals and adsorption of protein, poly (ethylene-alt-maleic anhydride) (PEMA) and chitosan were used to coat TiO2 nanoparticles. The results confirmed that surface coating of TiO2 nanoparticles could reduce such toxicity after photoactivation, by hindering adsorption of biomolecules and generation of hydroxyl radical (·OH) during photoactivation.